Efeito da instituição da cobrança pelo uso da água na configuração agrícola irrigada em Cristalina-GO - Furquim, Maria Gláucia Dourado (2017)
The water availability to different user sectors and ecosystems, ensuring the quality, quantity and perpetuity of this resource for future generations, has been one of the challenges of public management, particularly in the sphere of River Basins committees. The present study is about the effectiveness of the institution of a fee, to be charged by the water use in the Paranaíba River Basin, with a forecast of charging from 2017. An exploratory and descriptive research was carried out to get information about the reality of irrigated agriculture in the county of Cristalina GO, which stands out nationally for having the largest area irrigated by central pivot of Latin America. Through the linear programming method, alternative scenarios were elaborated to the current configuration of land use by irrigated agriculture, resulting from the different collection values to be instituted gradually, starting in 2017, modeling the function/goal as a result of the maximum financial return given the restrictions on water availability and agricultural area. The results indicate that the fee will not imply a significant reduction of the total income of the irrigating producer to the point of instigating changes in the areas or cultures currently cultivated, however, the collected values are presented as a source of investments for the recovery/conservation of the water bodies of the basin itself .